La normatividad regulativa del orden cosmopolita kantiano - Sánchez Madrid, Nuria (Con-Textos Kantianos. International Journal of Philosophy, 2022)
Reseña de: Corradetti, Claudio, Kant, Global Politics and Cosmopolitan Law. The World Republic as a Regulative Idea of Reason, New York/Oxon, Routledge, 2020. ISBN: 978-0-367-03050-6